2020
DOI: 10.1155/2020/8068797
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Analysis and Safety Profile of Farmed Edible Bird’s Nest in Malaysia and Its Effect on Cancer Cells

Abstract: Edible bird’s nest (EBN) which is solidified swiftlet’s saliva contains high nutritional value. It is widely consumed in countries like Malaysia, Indonesia, and Thailand. However, previous proximate analysis of Malaysia EBN was not representative of all the regions in Malaysia. In recent years, safety issues such as high nitrate and nitrite contents, presence of heavy metal, adulteration, fungal infection, and cancer cell stimulation were associated with EBN. Hence, this study aimed to determine the proximate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
2
8
0
2
Order By: Relevance
“…The proximate composition of different shaped EBN, which are half cup and stripe-shaped, is shown in Table 3 . This present finding of proximate composition was in the range of the other reported literature [ 15 , 35 ], with protein being the major content, followed by carbohydrate, moisture, and ash, while no fat was detected (lower than the limit of detection, LOD). Interestingly, fiber was found to be present in both EBN.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The proximate composition of different shaped EBN, which are half cup and stripe-shaped, is shown in Table 3 . This present finding of proximate composition was in the range of the other reported literature [ 15 , 35 ], with protein being the major content, followed by carbohydrate, moisture, and ash, while no fat was detected (lower than the limit of detection, LOD). Interestingly, fiber was found to be present in both EBN.…”
Section: Resultssupporting
confidence: 85%
“…Moisture content found in the half cup and stripe-shaped EBN was 15.92 ± 0.08% and 19.51 ± 0.04%, respectively, which was relatively high compared with other studies, ranging from 7.50-14.00% [15,35]. However, another study had a similar range of moisture content as reported in this study (17.8-24.3%) [39].…”
Section: Proximate Analysissupporting
confidence: 62%
“…A proper cleaning process can reduce the nitrite and nitrate concentrations in EBNs (Chan et al, 2013;Hamzah et al, 2013). There are only limited studies (Quek et al, 2018;Tan et al, 2020) comparing the levels of nitrite and nitrate in house/farmed EBNs from different regions. Most studies compared between houses and cave/wild EBNs.…”
Section: Nitrate and Nitrite Content In Ebnmentioning
confidence: 99%
“…Although the nitrite and nitrate in the cave EBNs are significantly higher than the house EBNs on average, it can be seen from the Table 2 that the readings between the samples are widely distributed and the standard deviation value is high, especially in the cave EBNs. These nitrite and nitrate changes may be attributed to different cave and swiftlet farm environments, such as humidity, pH and climate; age of EBN when harvesting (harvesting time); contamination during harvest and the cleaning processes of the collected EBNs may all cause the different concentrations of nitrate and nitrate levels ( Paydar et al, 2013 ; Tan et al, 2020 ). The good management of the swiftlet houses, such as the frequent removal of swiftlet guano while the guano of the cave is left in the cave and not cleaned may contribute to lower nitrite level in the house nests.…”
Section: Nitrate and Nitrite Content In Ebnmentioning
confidence: 99%
See 1 more Smart Citation